Chromosomal evolution in Gekkonidae. I. Chromosome painting between Gekko and Hemidactylus species reveals phylogenetic relationships within the group - Trifonov, Vladimir A.; Giovannotti, Massimo; O'Brien, Patricia C. M.; Wallduck, Margaret; Lovell, Frances; Rens, Willem; Parise-Maltempi, Patricia P. [UNESP]; Caputo, Vincenzo; Ferguson-Smith, Malcolm A. (Springer, 2011)
Geckos are a large group of lizards characterized by a rich variety of species, different modes of sex determination and diverse karyotypes. In spite of many unresolved questions on lizards' phylogeny and taxonomy, the karyotypes of most geckos have been studied by conventional cytogenetic methods only. We used flow-sorted chromosome-specific painting probes of Japanese gecko (Gekko japonicus), Mediterranean house gecko (Hemidactylus turcicus) and flat-tailed house gecko (Hemidactylus platyurus) to reveal homologous regions and to study karyotype evolution in seven gecko species (Gekko gecko, G. japonicus, G. ulikovskii, G. vittatus, Hemidactylus frenatus, H. platyurus and H. turcicus). Generally, the karyotypes of geckos were found to be conserved, but we revealed some characteristic rearrangements including both fissions and fusions in Hemidactylus. The karyotype of H. platyurus contained a heteromorphic pair in all female individuals, where one of the homologues had a terminal DAPI-negative and C-positive heterochromatic block that might indicate a putative sex chromosome. Among two male individuals studied, only one carried such a polymorphism, and the second one had none, suggesting a possible ZZ/ZW sex determination in some populations of this species. We found that all Gekko species have retained the putative ancestral karyotype, whilst the fission of the largest ancestral chromosome occurred in the ancestor of modern Hemidactylus species. Three common fissions occurred in the ancestor of Mediterranean house and flat-tailed house geckos, suggesting their sister group relationships. PCR-assisted mapping on flow-sorted chromosome libraries with conserved DMRT1 gene primers in G. japonicus indicates the localization of DMRT1 gene on chromosome 6.
Keywords: comparative chromosome painting; karyotype evolution of lizards; Gekkonidae; DMRT1; sex determination